2019
DOI: 10.12973/eu-jer.8.3.753
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of STEM-Based on Gender Differences: The Impact of Physics Concept Understanding

Abstract: The purpose of this research is to describe the effectiveness of STEM on the physics concepts understanding seen from gender differences. The research method used is a type of quasi-experimental design with 2x2 factorial design and saturated sampling technique. The data collecting technique used a tested method to see the results of students' concept understanding. Hypothesis testing was done using two-way ANOVA 2 x 2 factorial designs. The results of the study are: (1) there are differences in STEM and conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 26 publications
4
54
0
9
Order By: Relevance
“…They found that the DI learning model is more appropriate to be applied to students with the quitter type of AQ. This is in line with the research of Sagala et al (2019) which proves that the conventional model does not have a major influence on students' understanding of scientific concepts. However, the results of this research indicate that DI can improve students' divergent-thinking skills viewed from their AQ although the result for each type of AQ has a quite high range of scores.…”
Section: Discussionsupporting
confidence: 90%
“…They found that the DI learning model is more appropriate to be applied to students with the quitter type of AQ. This is in line with the research of Sagala et al (2019) which proves that the conventional model does not have a major influence on students' understanding of scientific concepts. However, the results of this research indicate that DI can improve students' divergent-thinking skills viewed from their AQ although the result for each type of AQ has a quite high range of scores.…”
Section: Discussionsupporting
confidence: 90%
“…Most advances in learning have been made possible by effective teachers (Yamtim et al, 2014). Effective teaching and learning determine the ability of students to understand and assimilate the information received particularly in the sciences (Lupascu et al, 2014;Sagala et al, 2019). Effective learning in educational institutions requires effective teachers and good teaching methods (Ates & Kadioglu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, physics is also a mean for developing thinking skills and problem-solving skills for the students. Besides, physics material is closely related to events that we experience in everyday life (Pareken, Patandean & Palloan, 2015;Sagala, Nuangchalerm, Saregar & El Islami, 2019;Sagala, Umam, Thahir, Saregar & Wardani, 2019;Sulistyaningrum, Prihandono & Subiki, 2015).…”
Section: Introductionmentioning
confidence: 99%